The Future Of The Profession Of Accountant Sharia Enter MEA In 2017 - Arwani, Agus (International Journal of Islamic Business and Economics (IJIBEC), 2017)
Accountant sare the actors who contribute to the establish ment and implementation of accounting as a structure. On the other hand the consequences of the application of modern accounting shows the impact of a less than satisfactory. Facts show the number of accounting manipulation scandal that hit the company's financial statements and the low awareness of their social responsibility and the environment implies that very large changes in accounting principals. Accounting reality is part of how accountants take on the role. Deviations reality always brings accountants as party central is how actors and structures form mutually met. Habitus actor '' greedy '' met with accounting (capitalism) as a structure that legitimize it. In reality accountant (agent) looks so lost in the shackles of capitalism, so the agency theory in the form of a conCict of interest, it seems to shift the basis of mutual symbiosis between the interests of management and accountants. Accountants must be returned khittah her as a sovereign profession, he is an ideologue as Rausyan Fikr. All forms of deep−an accountant in worship, glorify the '' number '' in the sense of making all tasks as tasks (treatises) '' prophetic '' to map the right stakeholders fairly and correctly. This can only take place within the frame sovereign and raise awareness of the Godhead (fervently) to put God at the summit toward accountability. Readiness accountant sharia in entering the MEA in 2017 with preparing the capabilities and expertise of sharia−based accounting standards IFRS, Accounting Sharia must understand the risks of sharia, sharia accounting should be standardized SDI International, science and technology capabilities accountant sharia be reliable.